SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169118-ms
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Stability Analysis of Surfactant Floods

Abstract: Recent surfactant flooding experiments have shown very efficient oil recovery can be obtained without mobility control when the surfactant solution is injected below the critical velocity required for a gravity-stable displacement. The purpose of this study was to develop a method to predict the stability of surfactant floods at the reservoir scale based on gravity-stable surfactant flooding experiments at the laboratory scale. The scale up process involves calculation of the appropriate average frontal veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In their test, the breakthrough recovery decreased as the capillary number increased with the exception of lowest injection rate (1 mL/min), and the major difference between conventional oil and heavy oil waterfloods accounted for that at water breakthrough, and residual heavy oil was bypassed due to adverse mobility ratio, not from capillary trapping. The importance of frontal stability of surfactant flooding without mobility control at velocity less than critical one required for a gravity stable displacement was well studied [15,16]. Their studies indicated that higher velocity may cause unstable displacement front, which may not make the lowest residual oil saturation.…”
Section: A Different Cdcmentioning
confidence: 99%
See 2 more Smart Citations
“…In their test, the breakthrough recovery decreased as the capillary number increased with the exception of lowest injection rate (1 mL/min), and the major difference between conventional oil and heavy oil waterfloods accounted for that at water breakthrough, and residual heavy oil was bypassed due to adverse mobility ratio, not from capillary trapping. The importance of frontal stability of surfactant flooding without mobility control at velocity less than critical one required for a gravity stable displacement was well studied [15,16]. Their studies indicated that higher velocity may cause unstable displacement front, which may not make the lowest residual oil saturation.…”
Section: A Different Cdcmentioning
confidence: 99%
“…CDC has various applications in not only water flooding but also chemical flooding [12,13,15,16,40]. According to capillary number theory and critical capillary number requirement, to get best/highest oil recovery, the capillary number must be increased to two or three orders of magnitude [4], as can be seen from Figure 1.…”
Section: Cdc Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results and the proposed stability theory were found to be in good agreement. Tavassoli et al (2014aTavassoli et al ( , 2014b simulated these experiments and showed that fine-grid simlations could be used to predict the stable velocity. More recently, Tavassoli et al (2015) has extended the results to the reservoir scale and investigated optimization strategies using horizontal wells.…”
Section: Introductionmentioning
confidence: 99%